1990
DOI: 10.1021/bi00489a007
|View full text |Cite
|
Sign up to set email alerts
|

Affinity of phosphatidylcholine molecular species for the bovine phosphatidylcholine and phosphatidylinositol transfer proteins. Properties of the sn-1 and sn-2 acyl binding sites

Abstract: Both the phosphatidylcholine transfer protein (PC-TP) and the phosphatidylinositol transfer protein (PI-TP) act as carriers of phosphatidylcholine (PC) molecules between membranes. To study the structure of the acyl binding sites of these proteins, the affinity of 32 distinct natural and related PC molecular species was determined by using a previously developed fluorometric competition assay. Marked differences in affinity between species were observed with both proteins. Affinity vs lipid hydrophobicity (det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…In agreement with this study it was found that PC-TP prefers 1-palmitoyl-2-arachidonoyl-PC (C16:0/C20:4 PC) and 1-palmitoyl-2-docosahexanoyl-PC (C16:0/C22:6 PC) over any other naturally occurring PC species in vitro [10].…”
Section: Piis0014-5793(96)00770-3supporting
confidence: 90%
See 2 more Smart Citations
“…In agreement with this study it was found that PC-TP prefers 1-palmitoyl-2-arachidonoyl-PC (C16:0/C20:4 PC) and 1-palmitoyl-2-docosahexanoyl-PC (C16:0/C22:6 PC) over any other naturally occurring PC species in vitro [10].…”
Section: Piis0014-5793(96)00770-3supporting
confidence: 90%
“…It is striking that the majority (57%) of the endogenous bound PC species contain fatty acyl chains (C20:4, C20:5 and C22:5) which are precursors in the prostaglandin/leukotriene biosynthesis [21]. This may indicate that PC-TP is involved in the delivery of these species to sites containing receptor-controlled phospholipases A2 [10]. According to this model PC-TP plays a role in signal transduction similar to what is observed for PI-TP [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In transferring PC between membranes, PC-TP prefers PC molecular species that have a palmitic acid on the sn-1 position and polyunsaturated fatty acid (PUFA) on the sn-2 position [42]. It is conceivable that relocation of PC-TP to mitochondria increases the amount of 16:0/PUFA-PC species in the mitochondrial membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Given that specific binding sites exist for the sn-1 and sn-2 acyl chains (29), it appears that the sn-1 saturated acyl chain dictates the stability of the complex more prominently than the sn-2 unsaturated acyl chain. Previously, by measuring the equilibration of PC between protein and membrane interface, PC-TP was found to more readily bind PC species carrying a C16:0 acyl chain than a C18:0 acyl chain (30). This difference in apparent affinity reflects the rates at which the PC monomer associates and dissociates from PC-TP and the membrane interface in the collision complex between PC-TP and the membrane.…”
Section: Discussionmentioning
confidence: 99%